Accounting for higher education institutions - the impact of corporate social responsibility - Abreu, Rute (2011)
Accounting for Higher Education Institutions (HEI) is centred in the new public management practices developed in the management techniques of the private sector. Although in this research, higher education is a Big Option of the Plan and a budget priority adopted by the Portuguese Government; these produce several impacts on the Corporate Social Responsibility (CSR) of HEIs. If neither CSR nor accounting will subordinate to the other, then higher education must be a strategic imperative. We argue that HEI should promote a full disclosure of tri-dimensional accounting information that should be driven mainly by CSR principles. The empirical evidence is from a sample of 59 HEIs in Portugal. We seek to explain the factors that influence the implementation of the new accounting system in Portuguese HEIs and develop an exploratory factor analysis which analyzes the 106 original variables obtained from the survey. The results show diversification of sub-system, geographical location and legal status. Also, we discuss the behaviour of HEIs that present several difficulties in the implementation of management accounting and in the implementation of public official accounting plan, while considering accounting information useful and promoting the development of its execution. These factors will make understandable the new role of accounting to achieve the main objectives of the Bologna Process in Portugal, based on the CSR principles of transparency, accountability and sustainability.